Screening Out Neurodiversity - Wiggleton-Little, Jada (Kennedy Institute of Ethics journal, 2023)
Autistic adults suffer from an alarmingly high and increasing unemployment rate. Many companies use pre-employment personality screening tests. These filters likely have disparate impacts on neurodivergent individuals, exacerbating this social problem. This situation gives rise to a bind. On the one hand, the tests disproportionately harm a vulnerable group in society. On the other, employers think that personality test scores are predictors of job performance and have a right to use personality traits in their decisions. It is difficult to say whether these negative disparate impacts are a case of wrongful discrimination. Nevertheless, we will show that pre-employment personality tests prey on several features of autism in an unfair way, and for this reason, we suggest the contours of some regulation that we deem necessary.